Discourse on Islamic Education Regulation in Indonesia: Between Ideality and Reality - Margareta, Siska; Aprison, Wedra; Charles (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This article examines the purpose, methods, and challenges of Islamic education in Indonesia. Its primary goal is to cultivate Muslim individuals with noble character, deep religious knowledge, and a commitment to societal progress. The education process should integrate general and religious knowledge to enhance students' capacities. The article identifies three dimensions of Islamic education: spiritual, cultural, and intellectual. Despite increased government attention since 1945-1950, Islamic education institutions often remain under-recognized in the national system. Legal recognition has emerged, but challenges persist, particularly regarding the quality of human resources, as graduates often lack creativity. The article emphasizes the need for modern management and innovative methodologies to meet students' evolving needs. It positions Islamic education as vital, especially in rural areas, and concludes that enhanced support from the government and society is essential to improve its quality and relevance